Tayangan K-Drama Business Proposal dan Minat Mengonsumsi Kuliner Korea - Naftalena Dewi; Zainal Abidin; Nurkinan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence of the drama Business Proposal on interest in consuming Korean culinary delights. The independent variable in this research is the drama Business Proposal. The dependent variable in this research is interest in consuming Korean culinary delights. This research uses questionnaire data from the Sesang ID Team community with a sample of 78 people. This research uses uses and effect theory and a quantitative approach, which focuses on hypothesis testing using simple linear regression analysis. The results of this research show that the drama Business Proposal has an influence on interest in consuming Korean culinary delights with a significance value of 0.000 < 0.05 and a calculated t value of 4.846 > t table 2.227